2020
DOI: 10.1101/2020.05.26.114033
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enantiomers of Chloroquine and Hydroxychloroquine Exhibit Different Activities Against SARS-CoV-2in vitro, EvidencingS-Hydroxychloroquine as a Potentially Superior Drug for COVID-19

Abstract: In all of the clinical trials for COVID-19 conducted thus far and among those ongoing involving chloroquine or hydroxychloroquine, the drug substance used has invariably been chloroquine (CQ) diphosphate or hydroxychloroquine (HCQ) sulfate, i.e., the phosphoric or sulfuric acid salt of a racemic mixture of R-and S-enantiomer (50/50), respectively. As a result, the clinical outcome from previous CQ or HCQ trials were, in fact, the collective manifestation of both R and Senantiomers with inherent different pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 73 publications
0
18
0
Order By: Relevance
“…HCQ is formulated as the racemate of its R and S enantiomers, and both were found to be active in vitro by blocking SARS-CoV-2 infection in the low micromolar range, with the S stereoisomer being slightly more active that the R stereoisomer. 12 Therefore, both the S and R enantiomers served as templates for virtual screening, and only the top GP generated from R -HCQ and S -HCQ forms for the final ranking of the single screened drug were selected. When more than one form of the screened drug ( e.g ., more than one enantiomer, more than one protomer, etc.)…”
Section: Methodsmentioning
confidence: 99%
“…HCQ is formulated as the racemate of its R and S enantiomers, and both were found to be active in vitro by blocking SARS-CoV-2 infection in the low micromolar range, with the S stereoisomer being slightly more active that the R stereoisomer. 12 Therefore, both the S and R enantiomers served as templates for virtual screening, and only the top GP generated from R -HCQ and S -HCQ forms for the final ranking of the single screened drug were selected. When more than one form of the screened drug ( e.g ., more than one enantiomer, more than one protomer, etc.)…”
Section: Methodsmentioning
confidence: 99%
“…A study conducted by Guanguan Li et al concluded that the enantiomers of CQ and HCQ act differently against SARS-CoV-2, and S enantiomers were found to be more effective. S enantiomers showed a better hERG inhibition and M pro activity in vitro as well as S-HCQ in vivo QT prolongation than R enantiomers [ 90 ].…”
Section: Pharmacological Treatment With Promising Clinical Benefitsmentioning
confidence: 99%
“…It has been demonstrated that S-CQ has a higher antimalarial activity than R-CQ [38]. Results from in vitro antiviral activity against SARS-CoV-2 in Vero E6 cells showed that both CQ and HCQ enantiomers exhibited antiviral effect in a concentration-dependent manner.…”
Section: Cq and Hcq Stereopharmacologymentioning
confidence: 99%